Outcomes of Colostomy Reversal in a Public Safety Net Hospital: The End or Beginning of a New Problem?. Issue 10 (October 2015) - Adam, Nadir; Rahbar, Shahrzad; Skinner, Ruby
Colostomy reversals can be technically challenging and linked to significant morbidity. There is sparse evidence that evaluates outcomes after colostomy reversals performed by acute care surgeons. We performed a review of 61 colostomy reversals from January 2011 to January 2014. Colostomies for acute diverticulitis were predominate, n = 32 (52%). Traumatic colorectal injuries were n = 15, 25 per cent. Colorectal cancer was n = 8, 13 per cent. Sigmoid volvulus accounted for n = 2 cases. Abdominal sepsis from adhesions was n = 3. A rectal foreign body was for n = 1 case. The time to reversal was 360 ± 506 days. Completion of reversals was successful in 90 per cent of cases and protecting stoma use was in n = 12, (22%). Surgical site infections occurred in n = 20, patients (32%). Surgical site infections were prevalent in obese patients, (55%). Anastomotic leaks (ALs) occurred at 12 per cent, and were prevalent in obese, [obese (22%) vs nonobese (8%), P = 0.1]. The majority of AL n = 6, (85%) were in acute diverticulitis and trauma. There were no ALs in cases with protective diversion. No deaths occurred. The elective nature of colostomy reversals does not imply low morbidity. Obesity and major inflammatory processes were associated with major surgical complications. These data suggest that protective stomas should be applied liberally, particularly in high-risk cases.